2016
DOI: 10.1017/s0954579416001218
|View full text |Cite
|
Sign up to set email alerts
|

Suicide ideation among high-risk adolescent females: Examining the interplay between parasympathetic regulation and friendship support

Abstract: Poor physiological self-regulation has been proposed as a potential biological vulnerability for adolescent suicidality. This study tested this hypothesis by examining the effect of parasympathetic stress responses on future suicide ideation. In addition, drawing from multilevel developmental psychopathology theories, the interplay between parasympathetic regulation and friendship support, conceptualized as an external source of regulation, was examined. At baseline, 132 adolescent females (M age = 14.59, SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 93 publications
(133 reference statements)
1
19
1
Order By: Relevance
“…Our findings on RSA reactivity seem inconsistent with results from two earlier studies: Crowell et al () reported that female self‐harming adolescents had elevated RSA reactivity to a sad film compared to controls, while Giletta et al () found that high levels of RSA reactivity to a stressor predicted suicidal ideation 9 months later. The discrepancy between the present findings and the just‐noted reports is likely to reflect substantial differences in sample characteristics, definitions of STBs, and data analytic approaches.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings on RSA reactivity seem inconsistent with results from two earlier studies: Crowell et al () reported that female self‐harming adolescents had elevated RSA reactivity to a sad film compared to controls, while Giletta et al () found that high levels of RSA reactivity to a stressor predicted suicidal ideation 9 months later. The discrepancy between the present findings and the just‐noted reports is likely to reflect substantial differences in sample characteristics, definitions of STBs, and data analytic approaches.…”
Section: Discussioncontrasting
confidence: 99%
“…First, all suicidal adolescents in our study had been clinically ascertained and were previously depressed. In contrast, suicidal subjects in the other studies either did not receive a psychiatric diagnostic assessment (Crowell et al, 2005) or included community-based subjects (Giletta et al, 2017). Second (not raw) scores to analyze physiological data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data collection occurred from 2010 to 2015 as part of a project examining interpersonal stress responses and trajectories of self-injurious thoughts and behavior (Giletta et al, 2016). Data from baseline and all follow-up time frames are reported here.…”
Section: Methodsmentioning
confidence: 99%